Genetic progress in physiological and biochemical traits related to grain yield in Moroccan durum wheat varieties from 1984 to 2007. Issue 1 (20th November 2021) - Boussakouran, Abdelali; El Yamani, Mohamed; Sakar, El Hassan; Rharrabti, Yahia
Abstract: Knowledge of the key physiological and biochemical traits related to genetic progress is essential to identify yield‐limiting factors and guide future breeding strategies. The aim of this research was to determine the rate of genetic gain in grain yield and physiological and biochemical traits in Moroccan durum wheat cultivars released from 1984 to 2007. Plants were subjected to two water regimes (irrigated and rainfed) during three growing seasons in order to identify those physiological and biochemical traits associated with grain yield. Grain yield (GY) and diverse physiological and biochemical traits known to be linked to mild drought stress were evaluated at anthesis and postanthesis. Physiological traits included stomatal conductance (gs ), transpiration rate (E), chlorophyll fluorescence (Fv /Fm ), chlorophyll content in flag leaf (SPAD), canopy temperature depression (CTD), and relative water content (RWC), whereas biochemical characteristics were leaf proline and water‐soluble carbohydrates (WSC) content. Grain yield tends to increase linearly under irrigated conditions with a genetic gain of 1.75% yr −1, in contrast, no significant change was observed under rainfed conditions. Traits that significantly increased over time were leaf proline content, gs, E, CTD, and SPAD. The changes in GY under irrigated conditions were largely explained by increases in gs during anthesis and postanthesis, CTD at postanthesis, and by leaf proline content at anthesis. Although genetic gains in GY under rainfed conditions could not be detected, leaf proline content and E were strongly associated to GY under these conditions, suggesting their usefulness as selection criteria for GY in water‐limited environments. Core Ideas:  Modern Moroccan durum wheat varieties tend to be more sensitive to drought.  No genetic gain in yield was found in Moroccan durum wheat evaluated under rainfed conditions.  gs and leaf proline content tend to change over time in six Moroccan durum wheat cultivars.  Yield was linked to gs, canopy temperature depression, and leaf proline content under irrigated conditions.  Under rainfed conditions, grain yield was related to E and leaf proline content.